2020
DOI: 10.4028/www.scientific.net/kem.856.360
|View full text |Cite
|
Sign up to set email alerts
|

Flexural Behavior of Compacted-Cement Sand Reinforced with Geogrid

Abstract: An improvement of flexural strength of cement stabilized soils using geogrid designated as compacted cement-geogrid-sand (CCGS) is investigated in this research. The studied material performance of the CCGS includes postpeak behavior, toughness, and equivalent flexural strength ratio. The geogrid inclusion significantly improves the postpeak flexural behavior, which is a requirement for bound pavement materials. The first peak flexural strength f1 and stiffness of both compacted-cement-sand (CCS) and CCGS are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Based on a series of laboratory tests, researchers have found that geogrid reinforcement can effectively delay the propagation and development of micro-cracks [ 2 , 4 ], significantly improving the flexural capacity of the components. The position and type of external loads applied, as well as the location and number of layers determined by the geogrid reinforcement design [ 4 , 5 , 6 , 7 , 8 , 9 ], will significantly impact the overall performance of cement-treated sand reinforced with geogrids (CTSGs). Some researchers have pointed out that matrix and reinforcement properties (including cement type, sand and gravel particle size distribution, geogrid type, etc.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on a series of laboratory tests, researchers have found that geogrid reinforcement can effectively delay the propagation and development of micro-cracks [ 2 , 4 ], significantly improving the flexural capacity of the components. The position and type of external loads applied, as well as the location and number of layers determined by the geogrid reinforcement design [ 4 , 5 , 6 , 7 , 8 , 9 ], will significantly impact the overall performance of cement-treated sand reinforced with geogrids (CTSGs). Some researchers have pointed out that matrix and reinforcement properties (including cement type, sand and gravel particle size distribution, geogrid type, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Numerous laboratory tests have demonstrated the feasibility and advantages of geogrid-reinforced cement mortar [ 4 , 5 , 6 , 7 , 8 , 9 ], but laboratory tests still have their limitations. With the development of discrete element numerical simulations, researchers have used numerical experiments to compensate for the shortcomings of laboratory tests, such as the difficulty in controlling variables and inability to conduct microscopic studies.…”
Section: Introductionmentioning
confidence: 99%